2024
DOI: 10.1136/tsaco-2023-001165
|View full text |Cite
|
Sign up to set email alerts
|

No healthcare coverage, big problem: lack of insurance for older population associated with worse emergency general surgery outcomes

Komal Abdul Rahim,
Namra Qadeer Shaikh,
Maryam Pyar Ali Lakhdir
et al.

Abstract: IntroductionOlder populations, being a unique subset of patients, have poor outcomes for emergency general surgery (EGS). In regions lacking specialized medical coverage for older patients, disparities in healthcare provision lead to poor clinical outcomes. We aimed to identify factors predicting index admission inpatient mortality from EGS among sexagenarians, septuagenarians, and octogenarians.MethodsData of patients aged>60 years with EGS conditions defined by the American Association for the Surgery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…In Pakistan, at the Aga Khan University Medical College, investigators have found in a secondary analysis of a large sample size that older patients who lack insurance have worse outcomes in EGS. 4 There were several very important take home messages from this manuscript. They found that the self-paid cohort had 17% higher odds of developing a complication than those with insurance and were operated on less frequently than those with insurance.…”
mentioning
confidence: 95%
“…In Pakistan, at the Aga Khan University Medical College, investigators have found in a secondary analysis of a large sample size that older patients who lack insurance have worse outcomes in EGS. 4 There were several very important take home messages from this manuscript. They found that the self-paid cohort had 17% higher odds of developing a complication than those with insurance and were operated on less frequently than those with insurance.…”
mentioning
confidence: 95%